Pengaruh Fasilitas Pembelajaran Dan Disiplin Belajar Terhadap Prestasi Belajar Matematika Siswa Kelas II SD Muhammadiyah 4 Kandangsapi Tahun Ajaran 2015/2016 - , Miranda Rizqi Fatmawati, Drs. Saring Marsudi, SH. M.Pd (2016)
ABSTRACT This study aims to determine: (1) the effect of learning facilities to students mathematics learning achievement of grade II SD Muhammadiyah 4 Kandangsapi the academic year 2015/2016 (2) the effect on the discipline of learning mathematics achievement grade II SD Muhammadiyah 4 Kandangsapi the academic year 2015/2016 (3) the effect of learning facilities and the discipline of learning the mathematics achievement of students grade II SD Muhammadiyah 4 Kandangsapi the academic year 2015/2016. This type of research is quantitative research. Subjects in this study are students of class II SD Muhammadiyah 4 Kandangsapi year 2015/2016. The data collection technique used was a questionnaire, and documentation. Mechanical testing instruments used are validity and reliability testing. Techniques used prerequisite test is the test of normality and linearity test. Data analysis technique used is multiple regression analysis, t-test, test- f, coefficient of determination and looking for the contribution given. The first hypothesis of the calculation results obtained t> t table (2.280> 2.002) and a significance value <0.05 (0.026 <0.05). From the calculation of the second hypothesis is obtained t> t table (5.672> 2.002) and a significance value <0.05 (0.000 <0.05). The third hypothesis of the calculation results obtained Fhitung> F table (75.502> 3.15) and a significance value <0.05 (0.000 <0.05). So that the conclusions of this study are (1) Facility Learning affect the learning achievement of Mathematics grade II SD Muhammadiyah 4 Kandangsapi (2) Discipline Learning to affect the learning achievement of Mathematics grade II SD Muhammadiyah 4 Kandangsapi (3) Facilities Study and Discipline learning effect on achievement studying Maths grade II SD Muhammadiyah 4 Kandangsapi. Keywords: learning facilities, learning discipline, and learning achievement